Productivity and Global Value Chains: A Tale from the Indonesian Automobile Sector - Padang Wicaksono; Yulial Hikmah; Rayinda Nur Ilmiawani (Economies, 2023)
Low productivity and quality of employment have always been a big problem in Indonesia, caused by the lack and mismatch of skills in the workforce. Labor productivity (LP) describes the company’s ability to produce something. This can be determined by added value or output. Several factors influence LP, such as education, age, and training. The concept of global value chains (GVCs) has become an integral part of economic activity, and trade within global production networks has grown more rapidly than conventional trade in final goods. GVCs have both positive and negative impacts on employment opportunities. The automotive industry is categorised as one of the ten primary priority industries in the Indonesian manufacturing sector. This research analyses the impact of LP on GVC integration in the Indonesian automotive industry. The data used in this research comes from the World Input–Output Database (WIOD) and the Central Statistics Agency (BPS) from 1995 to 2014. The variables used include the number of workers, added value, real wages, and GVC, which were calculated by the author using the Inter-Country Input–Output (ICIO) approach. Using ICIO analysis, the following matrix should be constructed to determine involvement in GVCs. This research shows that LP in the Indonesian automotive industry has a positive trend, and the GVC position in the Indonesian automotive industry has a positive trend line. The domestic value chain increased from 4% to 33%. This improves the ability to produce higher value-added and intermediate export goods. LP increases the domestic value chain in the Indonesian automotive industry, leading to global value chain integration. Thus, LP goes hand in hand with integrating GVCs.